ANALISA APLIKASI CAKE BERDASARKAN PRINSIP DAN PARADIGMA INTERAKSI MANUSIA DAN KOMPUTER MENGGUNAKAN EVALUASI HEURISTIC - Kaffah, Salsabila Ayuni; Anshori, Iedam Fardian (STMIK KAPUTAMA, 2021)
With the many mobile applications and websites that offer online courses and learning, learning English has never been easier. On the other hand, the field of study of Human and Computer Interaction (HCI) is an important aspect that must be considered in an application/website design. Cake application is an English learning application that uses mobile media. Cake has been downloaded by over 50 million users on the Google Play store and is regarded as a competitor to Duolingo, which is claimed as the best application for learning English. As a result, Nielsen and Molich's heuristic evaluation method was used to analyze the cake application. This Cake Application analysis seeks to ascertain the relationship between application functions using the principles and paradigms of Human and Computer Interaction (HCI). Human, Technology, Ergonomics, and Usability are the aspects that are evaluated, and they are thought to have been adequately represented by usability testing using the heuristic evaluation method. The analysis has revealed that most aspects of the application receive a severity rating scale of 0 (perfect scale), indicating that the Cake application meets the aspects of Human and Computer Interaction.